Polarization‐Entangled Photon Pairs from Warm Atomic Ensemble with Magnetic Background Noise. Issue 3 (29th January 2023) - Bae, Jinhyuk; Park, Jiho; Yu, Ye Jin; Noh, Heung‐Ryoul; Moon, Han Seb
Abstract: Atomic ensembles are important quantum resources for the generation, manipulation, and quantum memory of entangled photons. In photonic quantum information based on atom–photon interactions, high‐quality entangled‐photon‐pair sources are essential for realizing quantum information networks consisting of channels to connect the nodes through atomic ensembles. Here, a proof‐of‐concept for controlling polarization‐entangled photon‐pair sources from atomic ensembles by an external magnetic field under a magnetic noise environment is demonstrated. In the unshielded magnetic field, the polarization entangled state of the photon pair could be optimized to the target state by adjusting the magnetic field in an atomic vapor cell. The polarization‐interference fringe, Bell's inequality value, quantum state tomography, and Hong–Ou–Mandel interference of the polarization entangled photon pairs from the cascade‐type 5S1/2 –5P3/2 –5D5/2 transition of 87 Rb according to the direction of the external magnetic field. Accordingly, a magnetic field is found to be a promising means for controlling entangled two‐qubit states based on atom–photon. Abstract : Entangled photon sources based on atom–photon interactions are an essential requirement in the realization of several quantum information science researches based on photonic quantum systems. This work demonstrates the first ever control of polarization‐entangled photon pairs from a warm atomic ensemble of 87 Rb atoms by applying an external magnetic field in presence of the environmental magnetic noise.